2014
DOI: 10.5372/1905-7415.0805.332
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin response to supervised aerobic training in type II diabetic patients

Abstract: Background:Cross-sectional studies have linked decreased adiponectin levels with several metabolic traits, including insulin resistance, dyslipidemia, and metabolic syndrome. Previous studies conducted to investigate the effects of acute or chronic exercise on the serum adiponectin have produced conflicting and controversial results. Objective: To investigate the effect of supervised aerobic training of moderate intensity on the total serum levels of adiponectin and its relationship to insulin resistance and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These studies indicate that a significant volume of aerobic training is necessary to obtain a significant modification of Adiponectin levels and that this large volume can be reached both using long term interventions and high-intensity exercise protocols. Other authors recently confirmed the importance of prolonged exercise training (of at least moderate intensity) in order to obtain a significant increase in serum Adiponectin (Magkos et al, 2010): in fact, it was demonstrated that 12 weeks of moderate aerobic training significantly improved the total serum Adiponectin and high molecular weight Adiponectin in people with diabetes type II who generally have low serum Adiponectin levels (Aly et al, 2014). Furthermore, recent studies show that adiponectin expression is modulated by long-term physical activity in patients affected by Cystic Fibrosis and that, interestingly, in the active group cystic fibrosis patients adiponectin levels were inversely correlated with forced expiratory volume (FEV) 1% decrease/year and FEV1% decrease (Polito et al, 2019).…”
Section: Adiponectin and Exercisementioning
confidence: 89%
See 1 more Smart Citation
“…These studies indicate that a significant volume of aerobic training is necessary to obtain a significant modification of Adiponectin levels and that this large volume can be reached both using long term interventions and high-intensity exercise protocols. Other authors recently confirmed the importance of prolonged exercise training (of at least moderate intensity) in order to obtain a significant increase in serum Adiponectin (Magkos et al, 2010): in fact, it was demonstrated that 12 weeks of moderate aerobic training significantly improved the total serum Adiponectin and high molecular weight Adiponectin in people with diabetes type II who generally have low serum Adiponectin levels (Aly et al, 2014). Furthermore, recent studies show that adiponectin expression is modulated by long-term physical activity in patients affected by Cystic Fibrosis and that, interestingly, in the active group cystic fibrosis patients adiponectin levels were inversely correlated with forced expiratory volume (FEV) 1% decrease/year and FEV1% decrease (Polito et al, 2019).…”
Section: Adiponectin and Exercisementioning
confidence: 89%
“…Overall, in the last few decades, only a few studies with correct approaches have been found. In these studies, both aerobic and resistance training improved Adiponectin levels in about onethird of trials performed on sedentary, overweight and obese people (Cnop et al, 2003;Bouassida et al, 2010;Aly et al, 2014;Novaes Gomes et al, 2014;Dehghani and Mogharnasi, 2015).…”
Section: Adiponectin and Exercisementioning
confidence: 99%
“…At the last phase, all participants go into resting stage or cool-down, which continued for 10 to 15 min, where the workload decreased gradually until the participant's HR and blood pressure returned nearly to resting level. Throughout the entire training session, the heart rate of the participant was monitored using a portable heart rate monitor to maintain exercise intensity within the pre-calculated training heart rate [49].…”
Section: Assessment Of Physical Activitymentioning
confidence: 99%
“…AdipoR1 and AdipoR2 are present approximately in 1% of T cells, 93% of monocytes, 47% of B cells, and 21% of NK cells [24]. AdipoR2 mRNA expression and plasma concentration of adiponectin are decreased in patients with obesity, type 2 diabetes, and coronary heart disease [25][26][27].…”
Section: Discussionmentioning
confidence: 99%